Frameworks and Boundaries: constructing a curriculum armature for art. Issue 3 (2nd October 2022) - Granville, Gary
Abstract: This paper addresses some of the theoretical and practical implications of the Common European Framework of Reference for Visual Competency (CEFR-VC), developed through the European Network for Visual Literacy (Envil), in the context of international trends in curriculum design. Empirical application of the Framework is examined through the specific experience of designing a national programme for art in Ireland, for a high stakes public examination. The paper reflects on the issues that the Framework raised in that context. The paper suggests that a useful lens through which to view the framework might be that of activity theory and proposes that the framework itself might best be understood as a 'boundary-object' that can help inform the complex negotiations between art education and schooling.